Surgery for adhesive small-bowel obstruction is associated with improved long-term survival mediated through recurrence prevention: A population-based, propensity-matched analysis. Issue 3 (September 2019) - Behman, Ramy; Nathens, Avery B.; Haas, Barbara; Look Hong, Nicole; Pechlivanoglou, Petros; Karanicolas, Paul
Abstract : BACKGROUND: Adhesive small-bowel obstruction (aSBO) is among the most common reasons for admission to a surgical service. While operative intervention for aSBO is associated with a lower risk of recurrence, current guidelines continue to advocate a trial of nonoperative management. The impact of the increased risk for recurrence on long-term survival is unknown. We sought to explore the potential for improved survival with operative management through the prevention of admissions for recurrence of aSBO and the associated risks. METHODS: This is a population-based retrospective cohort study using administrative data. We identified patients admitted to hospital for their first episode of aSBO from 2005 to 2014 and created a propensity-matched cohort to compare survival of patients managed operatively with those managed nonoperatively. To test whether survival differences were mediated by recurrence prevention, a competing risk regression was used to model the subdistribution hazard of death when accounting for the risk of recurrence. An instrumental variable approach was used as a secondary analysis to compare survival while accounting for unmeasured confounding. RESULTS: There were 27, 904 patients admitted for their first episode of aSBO between 2005 and 2014. The mean age was 61.2 years (std dev, 13.6), and 51% were female. Operative management was associated with a significantly lower risk of death (hazard ratio, 0.80; 95% confidence interval, 0.75–0.86), which was robust to instrumental variable analyses, and a lower risk of recurrence (hazard ratio, 0.59; 95% confidence interval, 0.54–0.65). When adjusting for the risk of recurrence, operative intervention was not associated with improved survival, suggesting that the survival benefit is mediated through prevention of recurrences of aSBO. CONCLUSION: In patients admitted for their first episode of aSBO, operative intervention is associated with a significant long-term survival benefit. This survival benefit appears to be mediated through the prevention of recurrences of aSBO. STUDY TYPE: Retrospective cohort study. LEVEL OF EVIDENCE: Therapeutic study, Level II. Abstract : Supplemental digital content is available in the text.